The Effect of NelumboNucifera seeds and Hyphaene Thebaica on Induced Animal’s Hyperlipidemia and Hypertension (Medico Legal Update, 2021)
The life style of the people by large has been adversely affected due to manifold reasons which includesindustrialization and eventually making obesity as a very fast growing epidemic worldwide. Consequenceof overweight, results in chronic diseases like cardiovascular issues, diabetes, and cancer. Nearly everyobese person is found to be hyperlipidemia, which indicates a condition of having high levels of cholesterol,cholesterol esters, triglycerides, low-density lipoprotein and depleted levels of high-density lipoprotein. Thehigh frequency of side effects implications of the drugs available in the market has raised a dire need ofdiscovering and developing a new novel drug. The studies show that the plants have proven to be an uprightsource of natural as well as multifunctional molecules. The natural molecules flavonoids along with othercomponents have been reported for multi-functionality. HyphaeneThebaica and NelumboNucifera havedirect lowering effect on blood lipids and hypertension. This review explains the effect of HyphaeneThebaica(Doum) and NelumboNucifera (Lotus seeds) on blood lipids and hypertension. Lipid profile will be evaluatedby estimation of Cholesterol count , Triglycerides , High and low density lipoprotein while hypertensionwill be evaluated by measuring Aginotensin converting enzyme ( ACE) in serum and tissue extraction.Herbal medicine is the new good treatment for many chronic diseases to get ride from side effects of anticholestremicand anti-hypertension drugs.